The Management of KKG Gugus Mendut, Bulu sub district, Temanggung. - Widartono., Bambang (2010)
The research's purpose is to describe (1) the activity management of KKG Gugus Mendut Bulu sub district, Temanggung, (2) the problem management of KKG Gugus Mendut Bulu sub district, Temanggung. This research used qualitative approach. This research is done at KKG Gugus Mendut Bulu sub district, Temanggung. The main subject in this research is KKG chief, he guide lesson, and member of KKG program. Data collecting method used observation, interview, and documentation. Data analysis is started from (1) reduction data, (2) display data, and (3) drawing verification. The validity data is consisting of credibility, transferability, dependability, and conformability. The result's research shown (1) the activities at KKG Gugus Mendut is consist of work meeting, learning activity and evaluation activity. Work meeting in KKG is consist of work agenda meeting which has aim to complied the activity plan in KKG, manager meeting, and colossal meeting. The agenda meeting and manager meeting is done by schedule while the colossal meeting is according to the needed and problems which is faced. Another activity in KKG Gugus Mendut is activity learning, it is done with material that is fixed before. The learning activity is lead by the guide lesson and it is done every Saturday at 10.00 pm. learning activity model that is used in KKG Gugus Mendut is cooperative learning model which is involved the program member in learning activity, so that the learning activity is not concentrated in the lesson guide. Learning activity is done with various methods such as communicative, group discussion, question and answer and also idea exchange so that is can be develop to over wide the member knowledge and growing new ideas, task giving, grouping work, observation and so on. Learning evaluation in KKG is done towards the learning material that is given to the member of KKG program. Evaluation is done to know the lack and the problem solution that is faced in activity. Evaluation is also done towards fund usage in KKG implementation. (2) The problem solution in KKG activity is done through learning activity and also the meetings. The problem that is faced by teacher in learning activity is discussed together in forum and then they try to find the solution. Every member had opportunity to convey their idea and input in every problem solution that is faced in KKG so that the decision which is took in problem solution is not absolute in the chief hand or lesson guide.